The Duality of Technological Innovation and Dynamic Capabilities: The Micro-Foundation of China's Construction Machinery Industry's Rise up the Global Value Chain - XIA, WEIFU; Alwie, Aryaty Binti; Taasim, Shairil Izwan Bin; Jin, Wong Tze; Naning, Fatin Hana binti (Journal of Ecohumanism, 2024)
In the context of global value chain reconstruction, Chinese construction machinery enterprises are facing the dual challenges of technological innovation and global competitiveness improvement. Based on organizational learning theory and dynamic capability perspective, this study constructs a theoretical framework of dual integration of technological innovation (exploratory innovation and pioneering innovation) and dynamic capability, and explores its impact mechanism on the global value chain upgrading of Chinese construction machinery enterprises. The study adopts a mixed research method, combining large-scale patent data analysis and in-depth case study, and constructs a longitudinal data set of 146 Chinese construction machinery enterprises from 2005 to 2022. By using structural equation modeling, dynamic panel regression and machine learning algorithms, this study reveals the following main conclusions: (1) The relationship between technological innovation duality and the global value chain position of enterprises is inverted U-shaped, and there is an optimal equilibrium point; (2) Dynamic capabilities partially mediate the relationship between technological innovation duality and global value chain climbing, among which absorptive capacity and reconstruction capacity are particularly critical; (3) The degree of internationalization of enterprises positively moderates the impact of technological innovation duality on dynamic capabilities; (4) The quality of the institutional environment moderates the relationship between technological innovation duality and dynamic capabilities, and a high-quality institutional environment strengthens the positive relationship between the two. The theoretical contributions of this study are: (1) it expands the global value chain theory and incorporates the duality of technological innovation into the analytical framework; (2) it reveals the mediating mechanism of dynamic capability theory in innovation and value chain climbing, enriching the dynamic capability theory; (3) it provides new empirical evidence for organizational learning theory and clarifies the dynamic process of exploration and utilization equilibrium. At the practical level, the research results provide guidance for engineering machinery companies to formulate innovation strategies and enhance global competitiveness, and also provide a basis for the government to formulate industrial upgrading policies. Future research can further explore the long-term evolution path of technological innovation duality and its differences in cross-cultural contexts.